Now's the time : teaching jazz to all ages - Goodkin, Doug, ....- (San Francisco : Pentatonic Press, 2007)
This one-of-a-kind book combines practice, theory, aesthetics, history and a proven pedagogy in leading both children and adults in the joys of jazz. It features 70 activities for teachers to do with children based on the Orff approach to music education, a clear developmental sequence and a thorough analysis of the basics of the blues, jazz standards and improvisation. Activities are applicable to preschool, elementary and middle school students and adaptable to any age. They include games, speech, body percussion, movement, songs and arrangements for Orff instruments of classic jazz tunes. Included also is a Middle School curriculum with examples of children's work.
Keywords: Jazz ; muziek ; kinderen